Total Erythrocyte of Pangasianodon hypophthalmus Feed Containing Kersen Leaf Solution (Muntingia calabura L.) - M. Rizki Maulana; Iesje Lukistyowati; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTPangasianodon hypophthalmus is a fish with high market demand, but it is very susceptible to attack by the Edwardsiella tarda. One of the natural ingredients that can be used to prevent E.tarda attacks is Muntingia calabura.The research was carried out from 22 December 2019 to 5 February 2020 at the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, Riau University. This study aims to determine red blood cells of P. hypophthalmus that were given kersen leaf solution and were challenged with E.tarda. The method used was experiment of Completely Randomized Design (RAL) with one factor, five treatments and three replications. The treatment used Kn: Negative control (feeding without adding kersen and not being challenged with E. tarda), Kp: Positive control (feeding without adding kersen and being challenged with E.tarda), P1: Feeding with the addition kersen of 1 ml/Kg, P2: Feeding with the addition kersen of 2 ml/Kg, P3: Feeding with the addition kersen of 3 ml/Kg. Blood sampling was carried out 3 times, namely at the beginning of the maintenance, the 30 day post-maintenance day and the 15 day after the challenge, the challenge test was carried out on the 31 post-maintenance day.The parameters observed were the number of erythrocytes, hemoglobin levels, hematocrit values, growth in absolute weight, survival rate and water quality. The results shown that feeding containing kersen leaf solution (Muntingia calabura L.) may effect to the red blood cells of Pangasianodon hypophthalmus The best treatments of this research was P3 with total erythrocytes 2.58 x 106 cells/mm3, hemoglobin level 11.57 g/dL, hematocrit value 37.33%, absolute weight growth 16.73 g and survival rate 86.67%. The results of water quality measurements during maintenance are temperatures ranging from 26-30 °C, pH 5.4- 6.6, DO 3.6- 4.0 mg/L, and NH₃ 0.091-0.12 mg/L. Keywords: Pangasianodon hypophthalmus, Kersen Leaf Solution, Erythrocyte, Haemoglobin, Hematocrit